Nucleation and growth mechanism in the early stages of nickel coating in jet electrodeposition: a coarse-grained molecular simulation and experimental study. Issue 18 (11th April 2022) - Zhang, Fan; Liu, Shenggui; Wang, Fei
Abstract : A coarse-grained molecular dynamics model and the vertical three-electrode device with flow-injection function are established to reveal the influences of different growth conditions on the microscopic nucleation growth of coating. Abstract : In jet electrodeposition, microscopic nucleation and growth in the early stages of nickel coating are curcial and directly related to the consistency and reliability of the coating structure. We set up a three-electrode device with flow-injection function based on the vertical distribution and further studied the early stages of nanocluster formation corresponding to parallel and vertical distribution states. According to the nucleation diffusion and growth analysis, a coarse-grained molecular dynamics model is established for the first time to reveal the influences of different growth environments on the microscopic nucleation growth of the coating structure. Thus, the ion dynamic diffusion and nucleation kinetic mechanism could be further achieved, these vary under different electrodeposition conditions. In addition, the physical structure of the surface coating can be obtained by element analysis and density functional theory (DFT) calculations. These findings provide a theoretical and experimental basis for the efficient preparation of nickel coatings.